2017
DOI: 10.1097/pas.0000000000000872
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Spread Through Air Spaces Is an Independent Predictor of Recurrence-free Survival in Patients With Resected Lung Squamous Cell Carcinoma

Abstract: Tumor spread through air spaces (STAS) is a newly recognized pattern of invasion in lung adenocarcinoma. However, clinical significance of STAS has not yet been characterized in lung squamous cell carcinoma. In this study, we investigated whether STAS could determine clinical outcome in Japanese patients with lung squamous cell carcinoma. We reviewed tumor slides from surgically resected lung squamous cell carcinomas (n=216). STAS was defined as tumor cells within air spaces in the lung parenchyma beyond the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
94
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(105 citation statements)
references
References 27 publications
3
94
2
1
Order By: Relevance
“…As demonstrated in ADC (2) the extent of STAS was not relevant for prognosis (12). The prognostic impact of STAS in SCC was most recently confirmed in a series of 2016 cases from Japan (17). Thus, beyond budding and cell nest size which has previously been identified as prognostically relevant morphological parameters in SCC (18)(19)(20)(21), STAS seems to be another morphological feature to allow for a better prognostic stratification of SCC and potentially the establishment of a clinically meaningful grading system in the near future.…”
Section: Prognostic Impact Of Stasmentioning
confidence: 78%
“…As demonstrated in ADC (2) the extent of STAS was not relevant for prognosis (12). The prognostic impact of STAS in SCC was most recently confirmed in a series of 2016 cases from Japan (17). Thus, beyond budding and cell nest size which has previously been identified as prognostically relevant morphological parameters in SCC (18)(19)(20)(21), STAS seems to be another morphological feature to allow for a better prognostic stratification of SCC and potentially the establishment of a clinically meaningful grading system in the near future.…”
Section: Prognostic Impact Of Stasmentioning
confidence: 78%
“…As demonstrated in ADC (2) the extent of STAS was not relevant for prognosis (12). The prognostic impact of STAS in SCC was most recently confirmed in a series of 2016 cases from Japan (15). Thus, beyond budding and cell nest size which have previously been identified as prognostically relevant morphological parameters in SCC (16)(17)(18)(19).…”
mentioning
confidence: 78%
“…STAS is recognized in approximately 30-50% of lung adenocarcinomas (5,6). Furthermore, recent publications have reported that STAS coexistence in squamous cell carcinoma was also associated with poor clinical outcomes after surgery (7,8).…”
mentioning
confidence: 99%